Simulation study on mitigating manufacturing defects in vehicle steering knuckles - Yang, Cheng-Jung; Lien, Zih-An; Huang, Liqi; Chen, Po-Tuan (International journal of advanced manufacturing technology, 2025)
The application of aluminum alloy castings in vehicle structures demands exceptionally high dimensional accuracy and mechanical strength, particularly in critical load-bearing and control components such as steering knuckles. This study optimizes the casting process for specially shaped steering knuckle components by integrating computer-aided engineering technology to conduct numerical simulations and parameter adjustments, thereby minimizing casting defects and enhancing the quality of finished products. Cimatron software was employed for mold design and disassembly, while Pro CAST software was utilized for numerical analysis of the flow field and solidification behavior to assess the flow characteristics of aluminum melt, shrinkage cavity distribution, and the effects of thermal stress during solidification. By adjusting casting pressure, optimizing the mold flow channel design, and enhancing the cooling system, this study effectively reduces common casting defects such as shrinkage and porosity while improving filling uniformity and microstructural quality. The optimized process significantly enhances the mechanical properties and manufacturing stability of castings, ensuring that the final products meet the stringent strength and reliability standards required for vehicle structural components. This study not only presents an effective strategy for refining the steering knuckle casting process but also serves as a valuable technical reference for optimizing the manufacturing of high-precision aluminum alloy components.